The sorcery of color, identity, race and gender in Brazil - Nascimento, Elisa Larkin (Online Brazilian Journal of Nursing, 2003)
African ancestral values and demographic presence are crucial to the making of the Brazilian nation. Yet the tendency is to deny their identity in favor of a unitary concept of nationality and cultural homogeneity under the aegis of patriarchy and Western values.In the globalized world, feminists and formerly colonized peoples have defined identity as a political right; this is the source of the theory of multiculturalism. The critique of Western universalism and patriarchy leads us to question the terms in which this theory has been articulated and points to the need to interrogate whiteness.This critique, developed in the practice and thought of feminist and anti-racist social movements, including Afro-Brazilian movements in the period 1930-1968, contributes in largely unrecognized ways to the construction of post-modern thought.The concept of gender implies moving the focus of attention from women to the relations between men and women. A similar shift can be made in the study of race relations and of feminist thought. Thus, it is suggested that the traditional focus on “Blacks” or on “the Black problem” in Brazil is insufficient. In order to deal effectively with the issue of race, one must interrogate the silent, invisible and unarticulated hegemony of white identity as ethnicity. In this process, reason is found to critically analyze feminist thought from the perspective of non-Western cultures. The line of scientific research and thought initiated and inspired by Cheikh Anta Diop and the analysis of the social and linguistic structures of the Yoruba, an African people who contributed greatly to the formation of Brazilian culture, reveal common grounds and areas of coherence between feminist theory and Afrocentric or perspectivist anti-racist thought.The text explores the legacy and current presence of racism in Brazil in their relation to patriarchy. The Sorcery of Color is proposed as a metaphor for the Brazilian standard of race relations, which transforms a perverse system of racial domination into a pretense of anti-racist ideals and creates the category of Virtual Whiteness as its fulcrum of identity. These factors are traced in the literature of psychology and new tendencies like ethnopsychiatry and the study of whiteness are identified. Also, the emergence of new theoretical and therapeutic approaches in the clinical practice and theoretical production of a new generation of Brazilian African descendant psychologists is observed and characterized as the Afro-Brazilian Listeners Based on documentary research, Black movements in São Paulo and Rio de Janeiro (1914-1960) are examined in a critical analysis that emphasizes the aspects of identity and education. Frequently, distortion and omission of data occur in studies of these movements, which present a continuum and coherence in thought and practice over the twentieth century, and also contribute to the construction of post-modern thought. In education, the conclusion is that attending to the widely demonstrated need to overcome racial discrimination will depend on a new approach to gender and to African identity.